2010
DOI: 10.1101/gr.109553.110
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive annotation of the transcriptome of the human fungal pathogen Candida albicans using RNA-seq

Abstract: Candida albicans is the major invasive fungal pathogen of humans, causing diseases ranging from superficial mucosal infections to disseminated, systemic infections that are often lifethreatening. We have used massively parallel high-throughput sequencing of cDNA (RNA-seq) to generate a high-resolution map of the C. albicans transcriptome under several different environmental conditions. We have quantitatively determined all of the regions that are transcribed under these different conditions, and have identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
207
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(226 citation statements)
references
References 35 publications
17
207
1
1
Order By: Relevance
“…Previous studies have shown that NTRs have fewer and shorter exons, less protein-coding potential, and less tissue-specific expression than annotated protein-coding genes (Bruno et al, 2010;Lu et al, 2010;Wetterbom et al, 2010;Zhang et al, 2010;Aanes et al, 2011;Graveley et al, 2011). To determine whether endospermic and embryonic NTRs have similar features, we analyzed the structure, coding potentials, and expression levels of the NTRs.…”
Section: Discovery Of Ntrsmentioning
confidence: 99%
“…Previous studies have shown that NTRs have fewer and shorter exons, less protein-coding potential, and less tissue-specific expression than annotated protein-coding genes (Bruno et al, 2010;Lu et al, 2010;Wetterbom et al, 2010;Zhang et al, 2010;Aanes et al, 2011;Graveley et al, 2011). To determine whether endospermic and embryonic NTRs have similar features, we analyzed the structure, coding potentials, and expression levels of the NTRs.…”
Section: Discovery Of Ntrsmentioning
confidence: 99%
“…RNA interference (RNAi) in this organism has been recently discovered (Drinnenberg et al 2009). First reports on the transcriptome have been published, revealing an extensive antisense transcriptome (Bruno et al 2010;Sellam et al 2010;Tuch et al 2010).…”
mentioning
confidence: 99%
“…For example, experiments have revealed the widespread presence of antisense transcripts and untranslated regions of varying lengths, dependent both on cell state and environmental conditions [97,98,105]. In the case of the white-opaque switch, RNA-Seq analysis of sense-antisense transcript pairs showed a significant anti-correlation, suggesting that many antisense transcripts act to repress their sense counterparts [98].…”
Section: Investigation Of Chromatin Structure and Transcriptional Regmentioning
confidence: 99%
“…Most recent studies of gene expression have used RNA sequencing (RNA-Seq) to obtain greater sensitivity and to reduce bias in assayed gene targets. RNA-Seq studies have identified 600 novel coding and over 1000 noncoding transcripts in C. albicans, many of which are regulated by environment and cell state [97,98]. Transcriptional profiles have now been defined under a wide variety of conditions both in vitro and in vivo [99][100][101][102][103].…”
Section: Investigation Of Chromatin Structure and Transcriptional Regmentioning
confidence: 99%